Astragaloside IV Exerts Cardioprotection in Animal Models of Viral Myocarditis: A Preclinical Systematic Review and Meta-Analysis - Zhuang, Zhuang; Wang, Zi-Hao; Deng, Li-Hui; Zheng, Qun; Zheng, Guo-Qing; Wang, Yan (Frontiers in Pharmacology, 2019)
Astragaloside IV (AS-IV), the essential active component of astragalus, possesses diverse biological activities that have beneficial effects against cardiovascular disease. Here, we conducted a preclinical systematic review of 15 studies including 577 animals to establish the efficacy and potential mechanisms of AS-IV for animal models of viral myocarditis (VM). Six databases were searched from inception to October 2018. Application of the Cochrane Collaboration’s tool 10-item checklist and Rev-Man 5.3 software to analyze risk of bias of studies and data on outcome measures revealed study quality scores ranging from 2 to 5. Compared with the control group, AS-IV induced a marked decrease in mortality (P< 0.05), inflammation of myocardium and pathological score (P< 0.05) and cardiac enzymes expression (P< 0.05), and improved the function of the heart (P< 0.05). The potential mechanisms of AS-IV action were determined as anti-remodeling of myocardium (n=1), anti-virus (n=2), antioxidant (n=2), anti-inflammatory (n=6), anti-apoptosis (n=1) and alleviation of myocardial fibrosis (n=2). The collective results indicate that AS-IV exerts cardioprotective effects in animals with VM via multiple signaling pathways.